Implementasi Contextual Teaching Learning dalam Pembelajaran untuk Meningkatkan Keaktifan Siswa - Rosalina; Widyaswarani, Elyvia; Angga Saputra, Frasetyo; Aulia Nurcholis, Rahma; Fitroh Lutfiana, Ayun (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
Student engagement in learning is a crucial indicator of the success of the teaching and learning process. However, many students tend to remain passive during lessons. One approach that can enhance student engagement is Contextual Teaching and Learning (CTL). This study aims to explore the implementation of CTL and its impact on increasing student engagement through a narrative literature review (NLR). The literature review was conducted by analyzing various scholarly sources discussing the application of CTL in learning. The findings indicate that CTL consists of several key components, namely constructivism, questioning, inquiry, learning community, modeling, reflection, and authentic assessment. These components significantly contribute to increasing student participation, fostering critical thinking, and enhancing learning motivation. Additionally, CTL-based learning strengthens students’ social skills through more effective interaction and collaboration. Therefore, CTL serves as a relevant instructional strategy for educators in creating a more interactive, meaningful, and contextual learning environment